Tantangan Beragama di Era Posmodern: Memetakan Dinamika Spiritual dan Praktik Keberagamaan dalam Dunia Digital - Herlim, Leonardi; Fernando, Andreas (JURNAL TERUNA BHAKTI, 2024)
The postmodern era brings new challenges to religious practice, especially with the advancement of digital technology that changes the way individuals interact with faith and spiritual communities in this digital age. This article aims to map the spiritual dynamics that emerge in the context of the digital world, as well as how digital platforms affect traditional, conventional religious practices. Using a descriptive qualitative method with a literature review approach, it can be concluded that the experiences of adherents of various religions adapting to these changes, including the phenomenon of virtual rituals, online religious learning, and interactions between communities on social media show that while the digital world offers new opportunities for the dissemination and understanding of religion, there are also challenges related to spiritual authority, authenticity of practice, and ethical issues. Thus, the influence of the evolution of Virtual Media and Worship in Spiritual Identity Amidst Diversity and Pluralism. Playing an important role in ethics and Social Responsibility in Digital Religious Practices so that pluralism and Tolerance in Digital Religion must continue to be actualized to face religious challenges in the postmodern era. Abstrak Era posmodern membawa tantangan baru bagi praktik keberagamaan, terutama dengan kemajuan teknologi digital yang mengubah cara individu berinteraksi dengan iman dan komunitas spiritual di era digital ini. Artikel ini bertujuan untuk memetakan dinamika spiritual yang muncul dalam konteks dunia digital, serta bagaimana platform digital memengaruhi praktik keberagamaan tradisional yang komvesional. Menggunakan metode kualitatif deskritif dengan pendekatan studi literature, maka dapat disimpulkan bahwa pengalaman para penganut berbagai agama yang beradaptasi dengan perubahan ini, termasuk fenomena ritual virtual, pembelajaran agama online, dan interaksi antar komunitas di media sosial menunjukkan bahwa meskipun dunia digital menawarkan peluang baru untuk penyebaran dan pemahaman agama, terdapat juga tantangan terkait otoritas spiritual, autentisitas praktik, dan isu-isu etika. Sehingga pengaruh dari evolusi Media dan Ibadah Virtual dalam Identitas Spiritual di Tengah Keberagaman dan Pluralisme. Memainkan peran penting etika dan Tanggung Jawab Sosial dalam Praktik Keberagamaan Digital sehingga pluralisme dan Toleransi dalam Keberagamaan Digital harus terus diaktualisasikanuntuk menghadapi tantangan beragama di era posmodern.